SARS-CoV-2 epitopes inform future vaccination strategies - Shafqat, Areez; Omer, Mohamed H.; Ahmad, Omar; Niaz, Mahnoor; Abdulkader, Humzah S.; Shafqat, Shameel; Mushtaq, Ali Hassan; Shaik, Abdullah; Elshaer, Ahmed N.; Kashir, Junaid; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Immunology, 2022)
All currently approved COVID-19 vaccines utilize the S-protein as their immunogen. SARS-CoV-2 variants of concern (VOCs) contain mutations in the S protein, enabling them to escape infection- and vaccination-induced immune responses to cause reinfection. New vaccines are hence being researched intensively. Studying SARS-CoV-2 epitopes is essential for vaccine design, as identifying targets of broadly neutralizing antibody responses and immunodominant T-cell epitopes reveal candidates for inclusion in next-generation COVID-19 vaccines. We summarize the major studies which have reported on SARS-CoV-2 antibody and T-cell epitopes thus far. These results suggest that a future of pan-coronavirus vaccines, which not only protect against SARS-CoV-2 but numerous other coronaviruses, may be possible. The T-cell epitopes of SARS-CoV-2 have gotten less attention than neutralizing antibody epitopes but may provide new strategies to control SARS-CoV-2 infection. T-cells target many SARS-CoV-2 antigens other than spike, recognizing numerous epitopes within these antigens, thereby limiting the chance of immune escape by VOCs that mainly possess S-protein mutations. Therefore, augmenting vaccination-induced T-cell responses against SARS-CoV-2 may provide adequate protection despite broad antibody escape by VOCs.